2, 3-Carbamate mannosamine glycosyl donors in glycosylation reactions of diacetone-d-glucose. An experimental and theoretical study. (November 2021) - Morelli, Laura; Legnani, Laura; Ronchi, Silvia; Confalonieri, Laura; Imperio, Daniela; Toma, Lucio; Compostella, Federica
Abstract: The role of the cyclic 2, 3- N, O -carbamate protecting group in directing the selectivity of mannosylation reactions of diacetone-d -glucose, promoted by BSP/Tf2 O via α-triflate intermediates, has been investigated through a combined computational and experimental approach. DFT calculations were used to locate the transition states leading to the α or β anomers. These data indicate the preferential formation of the β−adduct with mannosyl donors either equipped with the 4, 6- O -benzylidene protection or without it. The synthetic results confirmed this preference, showing in both cases an α/β selectivity of 4:6. This highlights a role for the 2, 3- N, O -carbamate in sharp contrast with what described in the case of 2, 3- O -carbonate mannosyl donors. Graphical abstract: Image 1 Highlights: Two new 2, 3- N, O -carbamate protected mannosaminyl donors have been developed. Glycosylation reactions gave slightly preferential β-selectivities. 2, 3-O-carbamate mannosamines are viable donors in glycosylation to β-mannosides.